Pengaruh Model Pembelajaran Team Assisted Individualization Berbantuan Kartu SoalTerhadap Hasil Belajar Ekonomi - Ririn Oktaviani; Ai Nur Solihat; Yoni Hermawan (JURNAL PENA EDUKASI, 2026)
The low learning outcomes of students in Economics at SMA Negeri 2 Singaparna, evidenced by Grade XI Final Semester Assessment (PAS) scores falling below the Minimum Mastery Criteria (KKM), motivated this study. This research aimed to examine the effect of the cooperative learning model type Team Assisted Individualization (TAI) assisted by question cards on improving student learning outcomes in monetary and fiscal policy material. A quasi-experimental method with a pretest-posttest control group design was employed. The research population is students in grade XI of SMA Negeri 2 Singaparna for the 2025/2026 school year. Using purposive sampling, class XI 7 (n = 39) served as the experimental group and class XI 8 (n = 39) as the control group. Data were analyzed using an independent sample t-test. Results showed a Sig. (2-tailed) value of 0.000 < 0.05, confirming the hypothesis. The experimental class mean score (85.41) significantly exceeded the control class mean (78.05). Therefore, the TAI cooperative learning model assisted by question cards is proven effective in improving student learning outcomes.